Brivaracetam in the Treatment of Patients with Epilepsy—First Clinical Experiences - Zahnert, Felix; Krause, Kristina; Immisch, Ilka; Habermehl, Lena; Gorny, Iris; Chmielewska, Izabella; Möller, Leona; Weyand, Anna M.; Mross, Peter M.; Wagner, Jan; Menzler, Katja; Knake, Susanne (Frontiers in Neurology, 2018)
Objectives. To assess first clinical experiences with Brivaracetam (BRV) in the treatment of epilepsies. Methods. Data on patients treated with BRV from February to December 2016 and with at least one clinical follow-up were collected from electronic patient records. Data on safety and efficacy were evaluated retrospectively. Results. In total, 93 patients were analysed; 12 (12.9%) received BRV in monotherapy. Mean duration of follow up was 4.85 months (MD=4 months; SD=3.63). Fifty-seven patients had more than one seizure per month at baseline and had a follow-up of more than 4 weeks; the rate of ≥50% responders was 35.1% (n=20) in this group, of which five (8.8%) patients were newly seizure free. In 50.5% (47/93), patients were switched from Levetiracetam (LEV) to BRV, of which 43 (46.2%) were switched immediately. Adverse events (AE) occurred in 39.8%, with 22.6% being behavioural, and 25.8% non-behavioural. LEV-related AE (LEV-AE) were significantly reduced by switching to BRV. The discontinuation of BRV was reported in 26/93 patients (28%); 10 of those were switched back to LEV with an observed reduction of AE in70%. For clinical reasons, 12 patients received BRV in monotherapy, 75% were seizure free and previous LEV-AE improved in 6/9 patients. BRV-related AE occurred in 5/12 cases, five patients discontinued BRV. Conclusion. BRV seems to be a safe, easy and effective option in the treatment of patients with epilepsy, especially in the treatment of patients that have psychiatric comorbidities and might not be good candidates for LEV-treatment. BRV broadens the therapeutic spectrum and facilitates personalized treatment.